Strontium Cobalt Oxide Perovskite for Methane Dry Reforming - Cheng, C. K.; Chang, Ying Shi (Universiti Teknologi Malaysia, 2016)
We have prepared SrCoO3 perovskite employing a sol-gel citrate method and used as a catalyst for dry reforming of methane at the stoichiometric ratio and temperature of 1023 K. The catalyst was characterized by techniques such as N2 physisorption, X-ray diffraction (XRD) and scanning electron microscopy (SEM). The textural properties of the as-synthesized catalyst show BET specific surface area of 14.40 m2 g-1 with an average pore diameter of 49.21 Å. The powder XRD pattern confirms the formation of perovskite phase that can be indexed in an orthorhombic symmetry. Catalytic activity evaluation showed conversion of 20.0% for both CH4 and CO2 with concomitant production of syngas with H2:CO ratio of 0.37. A part of this work was supported by the Research University Grant (No. RDU140315) of Universiti Malaysia Pahang, Malaysia